Job retention schemes in Europe: A lifeline during the Covid-19 pandemic - Jan Drahokoupil; Torsten Müller (European Trade Union Institute (ETUI), 2021)
This paper analyses the job retention schemes implemented in response to the Covid-19 crisis, showing quantitative trends and differences in terms of expenditure on the schemes and the number of workers involved. The key focus is on a qualitative analysis of the schemes' key properties. In order to understand the diversity of job retention schemes implemented in the Covid-19 crisis, we first develop a typology, distinguishing between three underlying types: short-time work schemes, furlough schemes, and wage subsidies. We then provide a comparative overview of the different schemes implemented in the context of the crisis, considering their design as well as their size in terms of expenditure, and map adjustments made to them in the course of the crisis. The third section analyses the evolution of the take-up of the schemes in the course of 2020. The remaining sections discuss in detail such key properties as: eligibility criteria, the level of support for employees and employers, the role of collective bargaining and worker participation, dismissal protection, measures to avoid misuse, and training provisions. The paper concludes by drawing lessons from experiences with the Covid-19 pandemic in light of the discussion on whether and how permanent schemes should be established. It argues that the main issue is to find a design that balances the interests of all stakeholders. This would require meaningful financial participation on the part of employers, effective integration of the schemes into active labour market policies, and provisions to avoid misuse, including the effective involvement of worker participation and collective bargaining structures.
Keywords: 330; labor market policy; wage subsidy; wage replacement benefits; coronavirus; Europe; Arbeitsmarktpolitik; Lohnsubvention; Lohnersatzleistungen; Coronavirus; Europa